2016
DOI: 10.1186/s12302-016-0082-9
|View full text |Cite
|
Sign up to set email alerts
|

Accumulation and variability of maize pollen deposition on leaves of European Lepidoptera host plants and relation to release rates and deposition determined by standardised technical sampling

Abstract: BackgroundRisk assessment for GMOs such as Bt maize requires detailed data concerning pollen deposition onto non-target host-plant leaves. A field study of pollen on lepidopteran host-plant leaves was therefore undertaken in 2009–2012 in Germany. During the maize flowering period, we used in situ microscopy at a spatial resolution adequate to monitor the feeding behaviour of butterfly larvae. The plant-specific pollen deposition data were supplemented with standardised measurements of pollen release rates and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
64
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(64 citation statements)
references
References 37 publications
0
64
0
Order By: Relevance
“…Five publications were relevant for the food and feed (FF) safety assessment (in terms of toxicity and allergenicity), 13 publications pertained to the ERA or the IRM of maize MON 810 (most studies assessed the interaction of maize MON 810 with target organisms and non-target organisms). Three of the 18 publications, B € ottger et al (2015), Holderbaum et al (2015) and Xu et al (2015), have already been assessed by EFSA (EFSA, 2016b) or the GMO Panel (EFSA GMO Panel, 2016), and have concluded that no environmental safety concerns owing to maize MON 810 and Cry1Ab were identified.…”
Section: Existing Monitoring Networkmentioning
confidence: 99%
See 3 more Smart Citations
“…Five publications were relevant for the food and feed (FF) safety assessment (in terms of toxicity and allergenicity), 13 publications pertained to the ERA or the IRM of maize MON 810 (most studies assessed the interaction of maize MON 810 with target organisms and non-target organisms). Three of the 18 publications, B € ottger et al (2015), Holderbaum et al (2015) and Xu et al (2015), have already been assessed by EFSA (EFSA, 2016b) or the GMO Panel (EFSA GMO Panel, 2016), and have concluded that no environmental safety concerns owing to maize MON 810 and Cry1Ab were identified.…”
Section: Existing Monitoring Networkmentioning
confidence: 99%
“…(1) existing food and food ingredients produced from genetically modified insect resistant maize MON810; (2) feed consisting of and/or containing maize MON810, including the use of seed for cultivation; and of (3) (Hofmann et al, 2016) for previous environmental risk assessment conclusions and risk management recommendations on the cultivation of Bt-maize events MON810, Bt11 and 1507. EFSA supporting publication 2016;13 (7) …”
Section: General Surveillancementioning
confidence: 99%
See 2 more Smart Citations
“…EFSA , 2015. However, scientific controversies remain on the isolation distances and buffer zones necessary to protect these species (Hofmann et al 2016, Lang et al 2015.…”
Section: Introductionmentioning
confidence: 99%